Capacity and QoS Based Codebook Construction for MIMO Precoded Spatial Multiplexing Systems with Limited Feedback - 杭娟 佘锋 罗汉文 黄建国 (Shanghai jiao tong da xue xue bao, 2009)
This paper deals with the design and performance analysis of transmit precoder optimization for multiple input multiple output （MIMO） systems with limited feedback of channel state information. A capacity criterion based optimal codebook construction algorithm for MIMO precoded spatial multiplexing systems is presented. The optimal precoder structure combining precoding and power allocation is employed. Simulation results show that the capacity criteria based codebook can achieve higher capacity than that of equally power allocation based codebook of previous research.